Anterior Superior Iliac Spine to the Tibial Tuberosity Length - Samarendra Mahapatro MBBS, MD; Satish Mohanty MBBS, MD; Sandeep Kumar Panigrahi MBBS, MD, MBA; Rajib Kumar Ray MBBS, MD; Shruti Saraswat MBBS, MD (SAGE Publishing, 2017)
Orogastric tube (OGT) procedures are done in 20% of newborn unit cases. This study was contemplated to work out a formula to predict OGT length in terms of femur length in neonates and its agreement to existing standards. In this observational study, OGT length was estimated using NEMU (nose-ear-mid umbilicus) in 53 consecutive newborns. Their anterior superior iliac spine to tibial tuberosity length (AS-TT) was measured and equated using linear regression analysis in Stata. We further verified the accuracy of the new formula and comparison of time taken by both the methods. Strong positive correlation was seen between OGT and AS-TT ( r = .88). OGT length was 10.14 + 0.88 AS-TT, which can be used in neonatal intensive care unit newborns with greater accuracy and with lesser time than the classical method. Strong agreement levels were seen. AS-TT closely relates to the femur length and can be chosen as a guide as it is faster when compared to other methods.